SELECTING BEEF COWS ACCORDING TO THE SELECTION INDEX WITH REGARD TO THEIR NATURAL RESISTANCE IN THE CONDITIONS OF THE SANDS OF THE NARYN - AMANZHOL ZEINULLAEVICH ZINULLIN; ARUZHAN ERKINOVNA NUGMANOVA; ALMAGUL SULEIMENOVNA ALIBAEVA (International Journal of Pharma and Bio Sciences, 2016)
This article shows the results of selecting beef cows with regard to their natural resistance. The main purpose of the study was to develop and implement the index method for selecting breeding stock for its further reproduction, based on the indicators of natural resistance in animals. The live weight and the milk yielding capacity of the animals were determined by the standard method, and the index of each animal was also determined by these indicators. The phagocytic, lysozymic and bactericidal activity of blood serum in animals was determined by the standard method as modified by A. Z. Zeinullin and A. Alibaeva. The natural resistance of each animal was determined according to the averaged index in phagocytic, lysozymic and bactericidal activity, followed by calculation of the index for each animal. The selection index was calculated by the formula proposed by A. Z. Zinullin. Single-aspect selection of animals only by their main economically useful traits does not ensure full economic effect from beef cattle breeding. The necessity of developing and implementing the methods of selecting animals for breeding with regards to the natural resistance indicators has been urgent for a long time. The studies performed in this area provided very valuable results. Consideration of the natural resistance indicators in selection will create conditions for improving the indicators of natural resistance in animals, providing high enough efficiency of selection by the live weight.